Modelling continental range shift of the African elephant ( Loxodonta africana ) under a changing climate and land cover: implications for future conservation of the species - (:unkn) unknown (My University, 2021)
Climate and land use change are anticipated to alter the distribution of wildlife, due to their impact on the quantityand quality of forage availability, water cycle, as well as competition for key resources. Using an ensemble ofspecies distribution models (SDMs), we sought to predict changes in the distribution of the African elephant(Loxodonta africana) in response to climatic and land cover change in Africa. We found that African elephantdistribution is driven predominantly by changes in temperature followed by changes in precipitation and landcover. Our results show that 17.1% of the continent shows high suitability for L. africana under the current climaticconditions, while 56.6% is unsuitable under similar climatic conditions. The modelled current suitability showsthat high and moderately suitable areas for L. africana are predicted to occur in the eastern, southern and partof western Africa. In 2050, unsuitable area for elephants under Representative Concentration Pathway (RCP) 4.5and RCP 8.5 is projected to increase by 12.7% and 14.1%, respectively. In contrast, the highly suitable area forL. africana is projected to decrease by 51.3% and 67.6% under RCP 4.5 and RCP 8.5, respectively. Compared tothe current climatic conditions, in 2070 highly suitable areas for L. africana are projected to decrease by 74.5% and85.9% under RCP 4.5 and RCP 8.5 scenarios, respectively. Climate change and land cover change are expected toworsen and become one of the major drivers for the loss of several wildlife species like the African elephant due totheir impact on availability of water and forage. Therefore, conservation and management of elephant populationsunder global change calls for carefully designed migratory corridors and conservation of trans-frontier landscapesto enable dispersal of the elephants and other associated species to more conducive environments.
Keywords: African Research